Come to tea on Planet Zum-Zee - Mitton, Tony.; Parker-Rees, Guy (London : Orchard Books, 2006)
Aliens of different colors arrive on Planet Zum-Zee and have a party.
2.7
K-3
Keywords: Extraterrestrial beings -- Juvenile fiction; Parties -- Juvenile fiction; Extraterrestrial beings -- Fiction; Humorous stories; Parties -- Fiction; Stories in rhyme; Extraterrestrial beings -- Fiction; Humorous fiction; Parties -- Fiction; Stories in rhyme; Humorous fiction